Value and Limits of Routine Histology Alone or Combined with Glutamine Synthetase Immunostaining in the Diagnosis of Hepatocellular Adenoma Subtypes on Surgical Specimens - Paulette Bioulac-Sage; Saïd Taouji; Brigitte Le Bail; Laurent Possenti; Charles Balabaud (International Journal of Hepatology)
Immunohistochemistry is a valid method to classify hepatocellular adenoma (HCA). The aim was to test the performance of routine histology combined to glutamine synthetase (GS) staining to identify the 2 major HCA subtypes: HNF1α inactivated (H-HCA) and inflammatory HCA (IHCA). 114 surgical cases, previously classified by immunohistochemistry, were analysed. Group A comprised 45 H-HCAs, 44 IHCAs, and 9 β-catenin-activated IHCAs (b-IHCA), and group B, 16 b-HCA and unclassified HCA (UHCA). Steatosis was the hallmark of H-HCA. IHCA and b-IHCA were mainly characterized by inflammation, thick arteries, and sinusoidal dilatation; b-IHCA could not be differentiated from IHCA by routine histology. Group B was identified by default. A control set (91 cases) was analyzed using routine and GS stainings (without knowing immunohistochemical results). Among the 45 H-HCAs and 27 IHCAs, 40 and 24 were correctly classified, respectively. Among the 10 b-IHCAs, 4 were identified as such using additional GS. Eight of the 9 HCAs that were neither H-HCA nor IHCA were correctly classified. Conclusion. Routine histology allows to diagnose >85% of the 2 major HCA subtypes. GS is essential to identify b-HCA. This study demonstrates that a “palliative” diagnostic approach can be proposed, when the panel of specific antibodies is not available.